‘홍로’ 사과 과피 및 과육의 단백질체 비교 분석 - 정정성(Jung-Sung Chung); 최성환(Sung Hwan Choi); 김재호(Jae Ho Kim); 심수용(Soo Yong Shim); 모크 아드난(Moch R. Adnan); 장은실(Eun-Sil Chang); 손영걸(Young-Geol Sohn); 김윤희(Yun-Hee Kim); 김진국(Jin Gook Kim); 이증주(Jeung Joo Lee) (Weon'ye gwahag gi'sulji, 2021)
국내 육종 사과 품종인 ‘홍로’의 과피와 과육에서 발현되는 단백질체를 추출하여 이차원 전기영동으로 분리하였다. 그 결과대부분의 단백질들은 과피와 과육에서 유사한 정도로 발현되었으나, 30개의 단백질 spot들은 과피 또는 과육에서의 발현 정도 가 2배 이상 차이가 났다. 이들 중 25개는 과피에서, 5개는 과육에서 더 높게 발현되었다. 이들 단백질들을 MALDI-TOF/TOF로 분석한 결과, 과피에서 더 높게 발현된 단백질 spot들 중 18개는 각각의 기능을 갖는 단백질로 동정 되었고, 나머지 7개는기능이 밝혀지지 않은 것으로 동정되었거나 미동정 되었다. 과육에서 더 높게 발현된 단백질 spot들의 경우 2개는 각각의 기능을 갖는 단백질로 동정 되었고, 나머지 3개는 미동정 되었다. 과피에서 더 높게 발현된 단백질은 에틸렌의 생합성과 관련된1-aminocyclopropane-1-carboxylate oxidase homolog(spot 21번), 이차대사산물의 생합성과 관련된 acetyl-CoA acetyltransferase,cytosolic 1(spot 148), acetyl-CoA acetyltransferase, cytosolic 1-like(spot 316) 및 8-hydroxygeraniol dehydrogenase-like(spot 348), 광합성과 관련된 oxygen-evolving enhancer protein 1, chloroplastic(spot 210) 및 ribulose-1,5-bisphosphatecarboxylase/oxygenase large subunit(spot 273), 생체방어 및 스트레스 반응과 관련된 (+)-neomenthol dehydrogenase-like(spot 216 및 219), formate dehydrogenase, mitochondrial(spot 305), glutathione S-transferase-like(spot 483 및 484) 및acidic endochitinase SE 2-like, partial(spot 391 및 392), 항산화효소인 L-ascorbate peroxidase 2(spot 221), 알레르기 관련단백질인 MLP-like protein 34(spot 406), major allergen Mal d 1(spot 451 및 452) 및 major allergen Mal d 1.06A01(spot457)이었다. 한편 과육에서 더 높게 발현된 단백질은 protein folding과 관련된 chaperonin 60 subunit alpha 1, chloroplastic(spot 8) 및 탄수화물 대사와 관련된 NADP-dependent D-sorbitol-6-phosphate dehydrogenase(spot 380)이었다. 이상의 연구 결과들은 사과의 육종, 저장, 품질, 환경에 대한 내성 등과 관련된 광범위한 연구에 유용하게 이용될 수 있을 것으로 사료되었다. The proteome expressed in the peel and flesh of ‘Hongro’, a domestic breeding apple cultivar, wasextracted and separated by two-dimensional electrophoresis. Most of the proteins were expressed atsimilar levels in the peel and flesh, but 30 protein spots showed a difference of more than two timeshigher in expression level in the peel and flesh. Of these, 25 were higher in the peel and 5 werehigher in the flesh. By analyzing these proteins with MALDI-TOF/TOF, 18 of the protein spots thatwere higher in the peel were identified as proteins with their respective functions, and the remaining7 were identified as having unknown function or were unidentified. In the case of the protein spotsexpressed higher in the flesh, two were identified as proteins having respective functions, and theother three were unidentified. Proteins more highly expressed in the peel were 1-aminocyclopropane-1-carboxylate oxidase homolog (spot 21) related to the biosynthesis of ethylene; acetyl-CoAacetyltransferase (spot 148), cytosolic 1, acetyl-CoA acetyltransferase, cytosolic 1-like (spot 316)and 8-hydroxygeraniol dehydrogenase-like (spot 348) related to the biosynthesis of secondarymetabolites; oxygen-evolving enhancer protein 1, chloroplastic (spot 210), and ribulose-1,5-bisphosphate carboxylase/oxygenase large subunit (spot 273) related to the photosynthesis; (+)-neomenthol dehydrogenase-like (spot 216 and 219), formate dehydrogenase, mitochondrial (spot 305), glutathioneS-transferase-like (spot 483 and 484), and acidic endochitinase SE 2-like, partial (spot 391 and 392) related to thebiological defense and stress response; and antioxidant enzyme L-ascorbate peroxidase 2 (spot 221), MLP-like protein34 (spot 406), major allergen Mal d 1 (spot 451 and 452), and major allergen Mal d 1.06A01 (spot 457) related toallergies. On the other hand, proteins that were more highly expressed in the flesh were chaperonin 60 subunit alpha 1,chloroplastic (spot 8) related to protein folding, and NADP-dependent D-sorbitol-6-phosphate dehydrogenase (spot380) related to carbohydrate metabolism. These results will be useful in a wide range of studies related to applebreeding, storage, quality, and environmental tolerance. KCI Citation Count: 0